Poor Ranking of Universities in Nigeria: Causes, Implications and Way Forward - Ogunode, Niyi Jacob; Abubakar, Dr. Hussain A. (Researchparks Publishing, 2023)
The paper analyzed the factors responsible for poor ranking of universities in Nigeria. The paper also discussed the implications of the poorly ranked Nigerian universities and suggested measures to address the problems with view of improving the ranking performance in the nearly future. Primary and secondary data were used for the paper. The data were collected from online publications and print materials. The paper concludes that factors responsible for the poor ranking of universities in Nigeria includes; inadequate funding, poor data management, poor website design, inadequate staff, shortage of facilities, unstable academic calendar, political influence, bad leadership, indigenization of principal officers of tertiary institutions, non-defined internationalization Policies, poor reputation, low academic staff-to-student ratio, low doctorates-awarded-to-bachelor-degrees-awarded ratio, low doctorates-awarded-to-academic-staff ratio, low institutional income per staff, research reputation, low research income per staff low research productivity, poor citations (research influence), low proportion of international students, low proportion of international staff, low international collaboration and low industry income (knowledge transfer). Also, the paper identified bad international image, low attraction by International Students and low attraction by international academic staff are the implications of poorly ranked universities. To improve the universities ranking in Nigeria, the paper hereby recommended that the National Universities Commission should formulate national strategic plans and target on national ranking for Nigerian universities and asks universities to develop their strategic plan and set their target on ranking within a time frame; effective web policy and web development, effective data management, adequate funding, employment of adequate academic staff, provision of adequate infrastructure facilities, branding of Nigerian universities, capacity building for universities administrators, expansion of post-graduate schools in the universities to increase enrolment, effective research policy and programme, increment in the number of international student, number of international academic staff, embrace international collaboration of academic staff and internationalization of tertiary education in Nigeria.